Social Media And Msme Product Promotion In Digital Days: What Experts Say - Syam'un Syam'un; Bachtiar Sembiring; B.M.A.S. Anaconda Bangkara; Endang Fatmawati; Antoni Antoni (Enrichment : Journal of Management, 2022)
Being via online entertainment means to make companions, yet business exercises, for example, private company advancements (SMEs), are likewise effortlessly found via virtual social networking. To explain reality and suppositions above, we have visited a few distributions as logical proof from specialists, particularly in online entertainment and business advertising, which we then concentrated on cautiously to find a straightforward solution. The review interaction includes a data coding framework and data evaluation and a conclusion after completing inside and out translations to find solutions.. This study uses data that we found electronically in many books, scientific articles, and websites discussing social issues and small business products' marketing. So based on the study and discussion, we can say that social media and MSMEs are two things that cannot be separated because of the existence of social media that can transform products, especially in marketing because, in the digital era, all rely on electronics, especially in social media applications